APPLICATION OF EQUILIBRIUM SHORELINE MODEL IN ERETAN BAY, NORTH-WEST OF JAVA, INDONESIA - Rafsanjani - Nim: 15114061 , Abdurrahim
This research discusses the applicability of equilibrium shoreline parabolic model conditions towards Eretan Bay coastal conditions, impact of focus point position towards Parabolic Bay Shape Equation (PBSE) and the stability of shoreline in Eretan Bay based on parabolic model. Equilibrium shoreline is a shoreline that has reached a stable condition. The stable condition in this term is the absence of significant changes in the shape of the beach because the waves propagate perpendicular to the shoreline. To describe the parabolic model MEEPASOL (A Model for Estimating Equilibrium PArabolic-type ShOreLines) is used. MEEPASOL is used to calculate model parameters and predict the final shape of static equilibrium shoreline. The parabolic model is calculated based on two main parameters, i.e. 1) the control line which is the line that connecting the wave diffraction point and the control point, 2) the obliquity of wave comes in the form of an angle between the control line and wave crest line near diffraction point. From these parameters will be obtained three constant values C. The constant C is a value that varies with the obliquity of wave that obtained from the regression analysis of 27 shoreline that is assumed in equilibrium with an empirical approach. The results of this research reveals that equilibrium shoreline parabolic model is applicable for Eretan Bay coastal conditions. Parabolic Bay Shape Equation (PBSE) shows that the change in position of the focal point has an impact on the length of the control line and the angle of incident wave. At the position of a particular focal point would produce the optimal equilibrium shoreline position. Then the current condition of shoreline in Eretan Bay experiences dynamic equilibrium on the east side of the pier and west side of the control point also some parts of the shoreline is unstable.